On practical aspects of optimal modelling in boundary element method - A. Brański; R. Olszewski (Archives of Acoustics)
The paper is concerned with application of the BEM in the environmental noise problems. The main step of the BEM is the discretization of the boundary into elements. Using too many elements is not efficient. To eliminate this drawback, in this paper two ideas are proposed. First of them is the optimal discretization, and the second one is the solution of the modelling problem in rotated coordinates. Since the optimal discretization theory derived for the function of one variable, then only the 2D problem is considered. The commercial code SYSNOISE is used to solve the numerical examples. The results confirm the utility of the proposed ideas.